Patient safety culture in public hospitals of Ethiopia: A systematic review and meta-analysis - Gedion Asnake Azeze; Kirubel Eshetu Haile; Amanuel Yosef Gebrekidan; Gizachew Ambaw Kassie; Berhan Tsegaye Negash; Yordanos Sisay Asgedom (PLoS ONE, 2025)
Background Patient safety is a major health care challenge and is an issue of global concern. Poor healthcare system in Ethiopia, alongside increasing concerns for safety and patient safety culture, prompted to this systematic review and meta-analysis. Our systematic review and meta-analysis aims to determine the pooled prevalence of patient safety culture among healthcare providers in Ethiopia from studies that administered Hospital Survey on Patient Safety Culture (HSOPSC) tool. Method This study employed a systematic review and meta-analysis and followed the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines. We carried out a comprehensive search for studies in Science Direct, Medline, African Journals Online (AJOL), Excerpta Medical Database (EMBASE), Scopus and Google Scholar to identify relevant observational studies published in the English language. Data sources were searched on the 10th of October 2024 and updated the search on the 29th of March 2025. All selected articles met the inclusion criteria according to the Participants, Intervention, Comparison and Outcome (PICOS) criteria.. Random effects model meta-analysis using STATA version 15 statistical software was conducted to estimate the pooled prevalence with 95% confidence intervals (CI). Funnel plot and I2 test were used to check publication bias and heterogeneity between studies, respectively. Subgroup analysis and leave-out-one sensitivity analysis was done. Results Searches retrieved a total of 667. After removing duplicates, 610 remained. 138 studies were reviewed in full, but only 14, which included 5,901 health care providers, were considered in the final meta-analysis. The pooled prevalence of patient safety culture among health care providers in public hospitals of Ethiopia was 45.52% (95% CI: 41.27, 49.76; I2 = 91.3; p-value<0.001). Conclusion and Implications Patient safety culture among health care providers in Ethiopia remained poor. These findings underscore the need for increased focus on education and training, development of guidelines and policies for patient safety to integrate a patient safety culture into the existing health system. Additionally, integrating patient safety education and training topics early in pre-service curricula is crucial. Registration Registered in PROSPERO database with registration number of CRD42023407601